Baboiyen Interpretasi Lagu Tenggi Kekomposisi Pendekatan Populer Bergenre Folk - Hedrianto Hedrianto; Arif Anas; Susandra Jaya (Jurnal Musik Nusantara, 2023)
"Baboiyen" is a composition of karawitan music inspired by the traditional art form of Saluang Patiak Tigo, specifically the repertoire of the Tenggi song from the Ujung Jalan village in South Solok Regency, Minangkabau. Saluang Patiak Tigo is often presented in various traditional ceremonies and weddings. The inspiring Tenggi song repertoire features intriguing musical elements with fluctuating tones and a melodic journey that rises and falls, creating a captivating impression. "Baboiyen" is an expression of the artist's ideas and concepts, developing the modes of the Tenggi song into an engaging musical composition with a popular folk genre approach. Through this work, the creator aims to share their musical experiences, provide inspiration, and foster interest in the development of traditional music.